2004
DOI: 10.1046/j.1462-5822.2004.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylorigamma-glutamyltranspeptidase upregulates COX-2 and EGF-related peptide expression in human gastric cells

Abstract: SummaryGastric mucosa responds to Helicobacter pyloriinduced cell damage by increasing the expression of COX-2 and EGF-related peptides. We sought to investigate the bacterial virulence factor/s and the host cellular pathways involved in the upregulation of COX-2, HB-EGF and amphiregulin in MKN 28 and AGS gastric mucosal cells. H. pylori strain CCUG 17874 was grown in Brucella broth supplemented with 0.2% (2,6-dimethyl)-b b b b -cyclodextrins. The soluble proteins released in the culture medium by the bacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 52 publications
0
39
1
Order By: Relevance
“…In support of this, a previous study using bacterial culture supernatants from H. pylori to stimulate MKN28 cells showed that ␥-glutamyltranspeptidase present in the supernatant upregulates COX-2 expression (1). Conversely, other reports have indicated that the cag pathogenicity island is not involved in cox-2 gene expression induced by H. pylori (1,11). The discrepancy with our data could be explained by differences in the H. pylori strains used as well as the use of transformed cell lines in prior studies, which is in contrast to the conditionally immortalized cell model system employed in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…In support of this, a previous study using bacterial culture supernatants from H. pylori to stimulate MKN28 cells showed that ␥-glutamyltranspeptidase present in the supernatant upregulates COX-2 expression (1). Conversely, other reports have indicated that the cag pathogenicity island is not involved in cox-2 gene expression induced by H. pylori (1,11). The discrepancy with our data could be explained by differences in the H. pylori strains used as well as the use of transformed cell lines in prior studies, which is in contrast to the conditionally immortalized cell model system employed in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been previously reported that H. pylori can induce an up-regulation in both HB-EGF gene expression and ectodomain shedding in human gastric cells (35,36). In addition, it has been shown that gastrin stimulation results in the up-regulation of the HB-EGF gene in gastric cells transfected with CCK-2R (37).…”
Section: Resultsmentioning
confidence: 96%
“…It has been previously reported that H. pylori-induced HB-EGF gene expression is due to the action of g-glutamyltranspeptidase (GGT), a recently identified bacterial enzyme (35). It has been reported that there may be a direct interaction between the bacterial GGT and the HB-EGF promoter, possibly via an oxidative stress-mediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…(44) Helicobacter pylori, which has a major etiological role in human gastric carcinogenesis, induces the activation of EGFR signaling mediated by the cleavage of proHB-EGF to promote enhanced gastric epithelial proliferation and gastric neoplasia. (45)(46)(47) Furthermore, in vitro experiments have shown that addition of an anti-HB-EGF blocking antibody to human glioblastoma cells reduces proliferation by 30 -40% compared with the addition of normal goat IgG. (48) Inhibition of HB-EGF expression in myeloma cells with CRM197 or an anti-HB-EGF antibody results in the suppression of cell proliferation and induction of cell apoptosis.…”
Section: Cell Proliferationmentioning
confidence: 99%